Flying lessons: Malaysia and other airlines avoiding Pan Am's final destination. Issue 8 (13th July 2015) - Mark Thomas, Mr; Thomas, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article examines the strategic option of airlines facing a crisis. It analyses the current troubles faced by Malaysia Airlines (MAS). Having faced major crises in five months in 2014, the company has been saved only by nationalisation and has a very uncertain future. However, the article shows that the problems of the company can also be traced to bad strategic positioning and some poor management decisions. A comparison with the demise of another former premium airline, Pan American World Airlines (Pan Am), is drawn. Design/methodology/approach – The article draws upon over 100 research and press articles as well as discussion with managers in the airline industry. Findings – The article shows that bad luck certainly had a negative impact on MAS in 2014. However, just as with Pan Am, luck is not the sole explanation. Given that airlines cannot predict a disaster, maintaining a robust strategic position and healthy finances are vital their survival. Originality/value – By drawing parallels with history, the article gives a greater insight into the problems that one company has found itself in. It shows how companies need to be aware of the changing dynamics of an industry and to prepare for crises.